(untitled) (Bioscience Journal, 2020)
Leptospirosis is a zoonosis that affects several species of domestic and wild animals and is an important cause of economic losses in cattle in Brazil. In this study, we determined the prevalence of bovine leptospirosis in the Triângulo Mineiro region, Minas Gerais, Brazil, identified the most frequent serovars of Leptospira interrogans, and examine the renal pathological changes associated with the disease. Samples of blood serum and kidney fragments from 100 bovine females were collected in cattle abattoir. In the serological investigation 48% of the cows were positive. The serovars for which there were more reactive animals were Wolffi (24%), Hardjo (21%) and Hebdomadis (18%). Among the positive samples, 14/48 showed antibody titers greater than 1:100, and 70.83% of the seropositive animals responded to more than one Leptospira interrogans serovar. Only one farm did not have seropositive cows and in nine farms studied, six (66.66%) presented seropositive animals to the Hebdomadis serovar. At the histopathological examination, the most frequent microscopic lesions in positive animals were hyalinization (81.25%), congestion (81.25%) and hydropic degeneration (70.83%). However, these histopathological alterations were also found in kidneys of animals negative to serology, such as hyalinization (80.77%), congestion (48.07%) and hydropic degeneration (55.77%) and these findings are unrelated to positivity. Histopathological examination of the kidneys is not indicated to replace the serological diagnosis of leptospirosis, and may be used only as a complementary examination. Despite the low frequency of seropositive animals in the Triângulo Mineiro region, the disease is present in a large number of farms. Noteworthy is the high frequency of serovar Hebdomadis and it can be considered an emerging serovar in the region. The evaluation of the frequency of this serovar in other regions becomes important, and once verified should result in the recommendation of the inclusion of this serovar in the leptospirosis control.